Legal Protection Against Ecolabeling Misuse For Sustainable Development Goals: Indonesia–United States Comparison - Shuandy Shuandy; Dedi Harianto Dedi Harianto; Robert (Talenta Publisher, Universitas Sumatera Utara, 2026)
Greenwashing is a practice that emerges alongside with the development of public environmental awareness and constitutes abuse of eco-labeling through green marketing activities to gain profit while claiming to contribute to the achievement of the SDGs. But in reality it mislead consumers and pollute the environment thereby hindering its achievement. This study aims to examine the legal regulations of the misuse of ecolabeling in Indonesia in the context of achieving the SDGs; the legal liability of business actors toward consumers arising from the misuse of ecolabeling; and the comparative legal protection available to consumers in Indonesia and the United States against the misuse of ecolabeling. This research employs a normative juridical research method, focusing on legal norms carried out by means of literature studies to obtain secondary data consisting of primary, secondary, and tertiary legal materials, this research has a descriptive nature and uses statutory and conceptual approach. The Data were collected through document and literature studies. While qualitative analysis with deductive methods used in drawing conclusions. The findings reveal that the misuse of ecolabeling through greenwashing constitutes an unlawful act that harms consumers and the environment, thereby a clearer legal and effective enforcement is required. In Indonesia, business actors may be held liable through compensation claims brought by consumers, Consumer Protection NGOs (LPKSM), or qualified environmental organizations. A comparative analysis based on Lawrence M. Friedman's legal system theory demonstrates that the United States provides a more comprehensive legal framework through the Federal Trade Commission's Green Guides and the Federal Trade Commission's enforcement authority against deceptive environmental marketing claims. These findings may serve as a reference for strengthening Indonesia's legal framework to enhance consumer protection and support the achievement of the SDGs.